UNIVERSITY EXTENSION AND PUBLIC POLICIES: MANAGEMENT, CAREER AND BUSINESS SKILLS FOR INTEGRAL DEVELOPMENT (Interdisciplinary Studies Journal, 2025)
University extension should be understood in the context of Brazilian educational public policies, highlighting its role in integral human development. This study aims to analyze the role of university extension in the development of competencies in management, careers, and business within the framework of Brazilian educational public policies. It is a qualitative and documental study conducted through the analysis of official documents, legislation, scientific articles, and contemporary books that support extension as a formative practice linked to curricular integration and the connection between teaching, research, and social demands. The results indicate that extension, when articulated with the institutional pedagogical project, contributes to the development of essential competencies in leadership, innovation, and sustainability in higher education institutions. Furthermore, it is evident that extension enhances students' employability and promotes social innovation by connecting academic knowledge with community needs. It is concluded that university extension constitutes a strategic space for strengthening educational public policies and for improving the management of people, careers, and business, favoring the integral development of the individual. The valorization and strengthening of extension practices as an effective part of the formative process in Brazilian higher education institutions are recommended.
Keywords: University Extension; Educational Public Policies; People Management; Integral Human Development; Professional Competencies